2017
DOI: 10.4038/slvj.v63i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Body condition score in large pure bred dogs: a preliminary study on agreement between owner's perception and scientific evaluation

Abstract: SUMMARY: Obesity is a severe health issue among companion dogs. It may seriously impair the quality of a dog's life predisposing to many other disease conditions. Incorrect assessment of the body condition (BC) of their pets by the dog owners has been identified as an obstacle which would prevent early intervention in canine obesity. This study was designed to assess the degree of agreement between the dog owner's perception of their pet's BC and the scientific assessment of body condition score (BCS). Eighty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A previous work, on a Labrador dog cohort, demonstrated an association between low birth weight and increased risk of overweight at adulthood, assessed through the body condition score (BCS) [ 23 ]. This score, established by palpation and visual observation on a 9-point scale, is widely used for body composition assessment both in clinical practice and for research because it is inexpensive, non-invasive and provides immediate results [ 24 , 25 , 26 ]. Although its correlation with dual-energy X-ray absorptiometry and deuterium oxide dilution is well established [ 25 , 27 ], studies have shown its subjectivity [ 28 , 29 ] with the influence of scorer experience [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous work, on a Labrador dog cohort, demonstrated an association between low birth weight and increased risk of overweight at adulthood, assessed through the body condition score (BCS) [ 23 ]. This score, established by palpation and visual observation on a 9-point scale, is widely used for body composition assessment both in clinical practice and for research because it is inexpensive, non-invasive and provides immediate results [ 24 , 25 , 26 ]. Although its correlation with dual-energy X-ray absorptiometry and deuterium oxide dilution is well established [ 25 , 27 ], studies have shown its subjectivity [ 28 , 29 ] with the influence of scorer experience [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%